PENGARUH PERILAKU KEPEMIMPINAN, LINGKUNGAN KERJA, MOTIVASI DAN KOMPENSASI TERHADAP LOYALITAS GURU DI SMAIT NUR HIDAYAH SUKOHARJO - Budhi Hartanto; Istiatin; Kartika Hendra Ts (ITB AAS Indonesia Surakarta, 2025)
The purpose of this research is to examine and analyze the influence of principal leadership behavior on teacher loyalty at SMAIT Nur Hidayah. To examine and analyze the influence of work environment on teacher loyalty at SMAIT Nur Hidayah. To examine and analyze the influence of job satisfaction on teacher loyalty at SMAIT Nur Hidayah. To examine and analyze the influence of work compensation on teacher loyalty at SMAIT Nur Hidayah. This research uses a quantitative descriptive approach. The location of this research was conducted at SMA IT Nur Hidayah Sukoharjo. The sample consisted of 81 people or respondents. The sampling technique was total sampling technique (census). The results of this research are: The t-test related to Leadership Behavior (X1) on Teacher Loyalty at SMAIT Sukoharjo obtained results t count = 9.290 > t table = 1.991, so there is an influence between Leadership Behavior (X1) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y). The t-test related to Work Environment (X2) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y) obtained results t count = 6.667 > t table = 1.991, so there is an influence between Work Environment (X2) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y). The t-test related to Work Motivation (X3) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y) obtained results t count = 3.053 > t table = 1.991, so there is an influence between Leadership Behavior (X1) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y). The t-test related to Compensation (X4) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y) obtained results t count for Compensation (X4) = 4.417 > t table = 1.991, so there is an influence between Compensation (X4) on Teacher Loyalty at SMAIT Nur Hidayah Sukoharjo (Y). Keywords: Leadership Behavior, Work Environment, Motivation, Compensation, Teacher Loyalty